Bioactive phenolic constituents of some Ochnaceae of Cameroon - M-T. Martin, B. Bodo’, M-T. Martin; B. Messanga, A. Till’,; Tih, R. Ghogomu- (Malaysian Journal of Science, 2000)
25 Bioactive polyflavonoids from Lophira alata, L. lanceolata and Ochna calodendron were discussed. Structural elucidation was performed by spectral methods, notably 2D NMR: COSY, HNABC and NOESY